Bimbingan Kelompok Teknik Permainan Ular Tangga Bermuatan Humor untuk Mengurangi Stres Akademik Siswa SMK - Pramudita, Galuh Ayu; Atmoko, Adi; Hotifah, Yuliati (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Academic stress is a common psychological state among students, particularly in Vocational High Schools, arising when academic demands overwhelm an individual's coping abilities. Left unmanaged, this stress can negatively affect students' psychological well-being and academic performance. This study aimed to develop a humorous